Effective stabilization of arsenic in contaminated soils with biogenic manganese oxide (BMO) materials. (March 2020) - Wang, Ya-nan; Tsang, Yiu Fai; Wang, Huawei; Sun, Yingjie; Song, Yi; Pan, Xiangliang; Luo, Siyi
Abstract: The role of biogenic manganese oxide (BMO) materials on the stabilization of arsenic (As) in contaminated soil was investigated. Experimental results indicated that the addition of BMO was proved to be highly effective to stabilize As in soils. Bioavailable As content was decreased from 4.56 mg kg −1 in the control samples to 1.72–1.86 mg kg −1 in BMO-treated soils. X-ray absorption near edge structure (XANES) results confirmed that BMO was mainly responsible for oxidizing As(III) to As(V). Sequential extraction results indicated that the transformation of As fractions was from non-specifically adsorbed fraction to poorly-crystalline hydrous oxides fraction and residual fraction, which can decrease the risk of As in contaminated soils. Moreover, BMO had a higher efficiency in stabilizing As than two types of abiotic Mn oxides. High throughput sequencing analysis indicated that the bacterial community and diversity were significantly changed after BMO treatment. The abundance of Proteobacteria phylum, including Massilia, Phenylobacterium and Sphingomonas genera significantly increased with the increasing amount of BMO. These findings suggested that BMO can be considered as a low cost, high effectiveness and environmental friendliness material for the remediation of As contaminated soils. Graphical abstract: Image 1 Highlights: BMO was successfully used for the stabilization of As in soil. BMO effectively stabilize As in contaminated soil. Bacterial community was remarkably changed after BMO treatment. BMO had a higher efficiency in stabilizing As than abiotic MnO2 .